4. SURGICAL OUTCOMES OF URETEROPELVIC JUNCTION OBSTRUCTION IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics and evaluate the surgical outcomes of treating ureteropelvic junction obstruction (UPJO) in children at Nghe An Obstetrics and Pediatrics Hospital from 2020 to 2023.Materials and Methods: A retrospective analysis was conducted on pediatric patients diagnosed with UPJO who underwent reconstructive surgery using the Anderson-Hynes method. Data on clinical symptoms, imaging findings, surgical techniques, and postoperative outcomes were collected and analyzed.Results: Among 38 pediatric patients included in the study, the youngest age at surgery was 1 month, and the oldest was 14 years, with the majority being male (81.6%). Left-sided obstruction accounted for 73.7% of cases. The Anderson-Hynes reconstructive surgery achieved a success rate of 97.4%, with recurrent UPJO and urinary tract infections effectively managed. Postoperative ultrasound results demonstrated significant improvement in hydronephrosis and renal function.Conclusion: Early detection and surgical intervention for UPJO yield high treatment efficacy. Prenatal ultrasound plays a critical role in identifying cases requiring timely treatment, thereby minimizing long-term kidney damage.
Keywords: Ureteropelvic junction obstruction; Anderson-Hynes